Polar codes and polar processing for 6G wireless systems - Kai NIU; Jinchen DAI; Jinnan PIAO (Tongxin xuebao)
As the first type of channel code achieving the channel capacity,polar codes are an important candidate for the 6G data transmission.A polarized processing framework for the 6G systems was proposed.In this framework,in order to fulfill the requirement of ultra-reliable transmission,a high-performance coding scheme of concatenated polar code was designed to approach the channel capacity with finite-length.Then,the polar coded MIMO scheme was devised to match the requirement of the high spectrum efficiency.Finally,the scheme of polar coded non-orthogonal multiple access was investigated to improve the transmission capacity.All these schemes indicate that polar processing can dramatically boost the performance of 6G wireless transmission and become a promising direction.